2013
DOI: 10.1136/vr.101691
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features, outcome and prognostic factors in dogs diagnosed with non‐cortisol‐secreting adrenal tumours without adrenalectomy: 20 cases (1994–2009)

Abstract: The aims of this study were to describe the clinical features, the outcome and the prognostic factors of dogs with non-cortisol-secreting adrenal masses without adrenalectomy, and also to provide clinical data that can be useful for making decisions when managing dogs with these types of neoplasms. Medical records from 1994 to 2009 were reviewed and 20 dogs were included in the study. The results showed that mean age at diagnosis for dogs with non-cortisol-secreting adrenal masses was 12 years with no sex pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 29 publications
2
11
0
2
Order By: Relevance
“…Authors of one small study reported prolonged survival (mean, 13.1 months) in a group of dogs with mainly noninvasive non–cortisol‐producing tumors . Only 3 dogs in this study had vascular invasion into the vena cava, and, although none of the primary tumors grew significantly during the follow‐up period, caval thrombosis was progressive in all 3 . The results of hypofractionated stereotactic volumetric‐modulated arc radiotherapy were also reported recently in 9 dogs with invasive adrenal tumors .…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Authors of one small study reported prolonged survival (mean, 13.1 months) in a group of dogs with mainly noninvasive non–cortisol‐producing tumors . Only 3 dogs in this study had vascular invasion into the vena cava, and, although none of the primary tumors grew significantly during the follow‐up period, caval thrombosis was progressive in all 3 . The results of hypofractionated stereotactic volumetric‐modulated arc radiotherapy were also reported recently in 9 dogs with invasive adrenal tumors .…”
Section: Discussionsupporting
confidence: 75%
“…The results of conservative management are difficult to quantitate because data are scarce and few investigators report the results of noninterventional management. Authors of one small study reported prolonged survival (mean, 13.1 months) in a group of dogs with mainly noninvasive non–cortisol‐producing tumors . Only 3 dogs in this study had vascular invasion into the vena cava, and, although none of the primary tumors grew significantly during the follow‐up period, caval thrombosis was progressive in all 3 .…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Nesse caso optou--se pela ressecção cirúrgica da massa após avaliação da vascularização, contorno irregular da massa, posicionamento deslocando a veia cava caudal ventrolateralmente e o tamanho (4 cm de diâmetro aproximadamente) indicando malignidade. Em humanos a adrenalectomia é indicada somente em massas acima de 4-6 cm ou quando há invasão vascular, porém em veterinária, apesar de estudos que ajudam no manejo clínico, não há consenso sobre as recomendações ao se diagnosticar massa em adrenal [3,18].…”
Section: Discussionunclassified
“…The median survival time in dogs with ATs treated with mitotane were 10 and 15.6 months and in those treated with trilostane it was 14 months [69,70]. In both studies mitotane was used in a protocol for selective destruction to resolve the clinical signs and not for complete destruction of the AT and metastases.…”
Section: Medical Treatmentmentioning
confidence: 99%